A Discussion on the Activity Origin in Metal‐Free Nitrogen‐Doped Carbons For Oxygen Reduction Reaction and their Mechanisms. Issue 17 (3rd September 2015) - Wu, Kuang‐Hsu; Wang, Da‐Wei; Su, Dang‐Sheng; Gentle, Ian R.
Abstract The origin of oxygen reduction reaction activity in metal‐free N‐doped carbons has been a stimulating, yet unsolved issue for the rational design of cost‐effective electrocatalysts for fuel cells and metal–air batteries. At present, there are several inconsistent opinions on the materials chemistry and the mechanism of the oxygen reduction reaction (ORR) performed on this type of materials. This article provides a brief review of the current understanding of ORR processes and the history of electrocatalyst development. With special attention, the focus of the discussion is on the major contentions of the current opinions towards metal‐free N‐doped carbon chemistry and the arguments for the probable ORR mechanisms. By clarifying the fundamental aspects of each opinion, a converging consensus on N‐doped carbon electrocatalysts can be established and thus facilitate the substantial development of large‐capacity energy devices.